A pesquisa em parceria universidade e escola: uma cartografia de possibilidades - Reis, Marelise de Fátima Griebeler (Universidade do Vale do Rio do Sinos, 2010)
This dissertation broaches the partnership between University and School, and privileges the said and done of eight people from a research group. It aims at comprehending the texture of the research as partnership, University and School, potentiality the continuing education of the involved people. The study has a qualitative approach and it is anchored in Freire’s dialogical view of complex thinking. For data collection it was used the field notes, email and semi-structured interview. The analytical dimensions focus on the features and the paradigm of the research in partnership; in its guiding principles: dialogical, recursive and hologramatic; and, in the impacts from its exercise, with implications on the subject’s formation and in different institutions where they work. The main authors that assist the theoretical framework are Brandão (2003), Cunha (2008), Freire (1997, 2000, 2002), Morin (1996, 2005, 2007, 2008), Tardif (2000) and Triviños (2008). It was observed that the partnership enhances the form
Keywords: formação continuada; universidade e escola; pesquisa em parceria; continuing educa; university and school; partnership research; Ciências Humanas